KONSISTENSI PENGUKURAN VALUE AT RISK JANGKA PENDEK DAN JANGKA PANJANG PADA SAHAM PERBANKAN PAPAN ATAS DALAM INDEX LQ45 PERIODE 1 AGUSTUS 2007 – 1 AGUSTUS 2012 - HARYANTI, TUTIK (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Investment always has a risk, Value at Risk (VAR) is the concept standard for measuring market risk. VAR measures the worst expected maximum loss over a specific time interval at a given confidence level. A VAR calculation has three components must be considered: a time period, a confidence level and volatility. Time and confidence level affects the computation, now the question, are consistent historical simulation method for calculating the risk of shortterm and long-term? This paper research monthly VAR Indonesian exchange stock for observe consistency, 1 and 2 represent the short-term 3-year representing the medium and long term representing 5 years at confidence level 95% and 90%. And as the sample is banking stock index LQ 45 is Bank Central Asia Tbk, Bank Negara Indonesia (Persero), Bank Rakyat Indonesia (Persero), Bank Danamon Indonesia Tbk, and Bank Mandiri (Persero) Tbk. The result of this research is the single asset. Short, medium and long term VAR consistent at confident level 95% but not VAR 90 % does not fit at short and long term. This means confident levels affect the consistency VAR simulation histories calculation method.